2022
DOI: 10.1093/eurheartj/ehac184
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vascular disease in pulmonary hypertension due to left heart disease: pathophysiologic implications

Abstract: Aims Pulmonary hypertension (PH) and pulmonary vascular disease (PVD) are common and associated with adverse outcomes in left heart disease (LHD). This study sought to characterize the pathophysiology of PVD across the spectrum of PH in LHD. Methods and results Patients with PH-LHD [mean pulmonary artery (PA) pressure >20 mmHg and PA wedge pressure (PAWP) ≥15 mmHg] and controls free of PH or LHD underwent invasive haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 54 publications
5
81
1
2
Order By: Relevance
“…Impairments in dynamic RV-pulmonary artery coupling are more likely here given the observed hemodynamics and what is known from the literature. 2,3 Systemic vascular resistance with exercise was ≈30% higher in patients with PVD as Jha notes, but pulmonary vascular resistance with exercise was almost 300% higher, a difference of even greater importance given the heightened afterload sensitivity of the RV in HF with preserved ejection fraction. 4 Although exercise echocardiography was not performed in our study, others have shown dramatic limitations in RV-pulmonary artery coupling during exercise in patients with HF and PVD, 2,3 suggesting that the circulatory bottleneck existed in the pulmonary rather than systemic vasculature.…”
Section: In Responsementioning
confidence: 99%
“…Impairments in dynamic RV-pulmonary artery coupling are more likely here given the observed hemodynamics and what is known from the literature. 2,3 Systemic vascular resistance with exercise was ≈30% higher in patients with PVD as Jha notes, but pulmonary vascular resistance with exercise was almost 300% higher, a difference of even greater importance given the heightened afterload sensitivity of the RV in HF with preserved ejection fraction. 4 Although exercise echocardiography was not performed in our study, others have shown dramatic limitations in RV-pulmonary artery coupling during exercise in patients with HF and PVD, 2,3 suggesting that the circulatory bottleneck existed in the pulmonary rather than systemic vasculature.…”
Section: In Responsementioning
confidence: 99%
“…membrane diffusion (Dm) and capillary volume (Vc) in parallel with CO changes, is explanatory of the altered pulmonary perfusion pattern occurring in HFpEF, 24 definitively resulting in an increased dead space to tidal volume (VD/VT) ratio and inefficient VE 55 . Exercise‐induced dynamic congestion often overlaps as an additive reason for impaired gas exchange and vascular distensibility 56,57 . The elevated afterload and RV dysfunction sustains further impairment in lung perfusion and challenges cardiac dynamics through an unfavourable RV to LV diastolic interaction.…”
Section: Comorbidities and Extracardiac Contributors To Impaired Exer...mentioning
confidence: 99%
“…55 Exercise-induced dynamic congestion often overlaps as an additive reason for impaired gas exchange and vascular distensibility. 56,57 The elevated afterload and RV dysfunction sustains further impairment in lung perfusion and challenges cardiac dynamics through an unfavourable RV to LV diastolic interaction. This may be observed under maximal exercise quite early and even in HFpEF patients who are otherwise asymptomatic at rest.…”
Section: Abnormal Lung Mechanics Pulmonary Hypertension and Vascular ...mentioning
confidence: 99%
“…1 8 Studies concurred that independent of the underlying left heart pathology (HFpEF, aortic stenosis), patients with CpcPH have substantially worse symptoms and prognosis than those with IpcPH or no PH. Combined noninvasive and invasive studies (eg, the recent study by Omote et al 1 ) have improved our understanding of the mechanisms underlying the symptoms of patients with . Importantly, the studies compiling this evidence used the 2015 CpcPH definition as inclusion criterion (most often by using only the PVR ≥3 WU criterion).…”
Section: Editorialmentioning
confidence: 99%